2017
DOI: 10.1097/ede.0000000000000716
|View full text |Cite
|
Sign up to set email alerts
|

Cord Blood Bisphenol A Levels and Reproductive and Thyroid Hormone Levels of Neonates

Abstract: Our findings suggested that fetal BPA levels might be associated with changes in certain reproductive hormone levels of neonates in a sex-specific manner, though further investigations are necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 37 publications
0
23
2
Order By: Relevance
“…The Sapporo Cohort of the Hokkaido Study on Environment and Children's Health allowed another group to examine simultaneous measurement of cord blood BPA, sex steroids and other hormones at the time of delivery. This did not find associations between BPA concentrations and levels of estradiol, progesterone or testosterone (though did note a weakly positive association with prolactin) in infant girls (Minatoya et al 2017). Yet, given the relatively rapid metabolism of BPA, cord blood measurements may be a limited mechanism of assessing exposure, possibly reflected in the reports that only 83.2% of samples had detectable BPA levels.…”
Section: Human Studiesmentioning
confidence: 77%
“…The Sapporo Cohort of the Hokkaido Study on Environment and Children's Health allowed another group to examine simultaneous measurement of cord blood BPA, sex steroids and other hormones at the time of delivery. This did not find associations between BPA concentrations and levels of estradiol, progesterone or testosterone (though did note a weakly positive association with prolactin) in infant girls (Minatoya et al 2017). Yet, given the relatively rapid metabolism of BPA, cord blood measurements may be a limited mechanism of assessing exposure, possibly reflected in the reports that only 83.2% of samples had detectable BPA levels.…”
Section: Human Studiesmentioning
confidence: 77%
“…In human epidemiology, studies have reported changes in TH parameters as a function of BPA exposure in adults ( 56 , 57 , 58 , 59 ), including in pregnant women ( 60 , 61 , 62 ). In pregnant women, maternal BPA levels were inversely ( 62 ) or positively ( 60 ) associated with T 4 levels while two studies reported no association ( 61 , 63 ). In humans, inverse associations of BPA with TSH have also been reported in both sexes ( 60 ) and in other cases, only in women ( 61 ).…”
Section: Phenolsmentioning
confidence: 94%
“…Studies carried out in the general population and in mother/child cohorts showed positive [139][140][141], negative [142][143][144][145], and no associations between BPA exposure and serum T4 levels [143,[146][147][148][149][150][151], whereas the relationship with serum T3 levels was estimated in few studies, with different findings [139,141,142,149,150].…”
Section: Effects On Serum Th Levelsmentioning
confidence: 95%